2014
DOI: 10.1098/rspb.2014.0844
|View full text |Cite
|
Sign up to set email alerts
|

Do avian cooperative breeders live longer?

Abstract: Cooperative breeding is not common in birds but intriguingly overrepresented in several families, suggesting that predisposing factors, similar ecological constraints or a combination of the two facilitate the evolution of this breeding strategy. The life-history hypothesis proposes that cooperative breeding is facilitated by high annual survival, which increases the local population and leads to a shortage of breeding opportunities. Clutch size in cooperative breeders is also expected to be smaller. An earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
4
26
3
Order By: Relevance
“…While previous studies have not shown an association between cooperative breeding and maximum longevity in mammals [9] and birds [10], these results suggest that eusociality in mammals, as defined by Williams and Shattuck, is strongly associated with increased lifespans.…”
contrasting
confidence: 91%
“…While previous studies have not shown an association between cooperative breeding and maximum longevity in mammals [9] and birds [10], these results suggest that eusociality in mammals, as defined by Williams and Shattuck, is strongly associated with increased lifespans.…”
contrasting
confidence: 91%
“…Theoretical evidence to date therefore suggests that long life increases the likelihood of cooperation evolving. Consistent with this prediction, comparative analyses have demonstrated that cooperative breeders are longer lived than non-cooperative breeders [11,13,14]. This finding, however, is also consistent with the alternative prediction that long life evolves as a result of cooperative breeding: group living protects individuals from extrinsic causes of mortality, which thus selects for longer life [15,16].…”
Section: Introductionsupporting
confidence: 69%
“…Conversely, high promiscuity is more likely to undermine the evolution of cooperation in short-lived species because the indirect fitness benefits of helping are relatively low and the costs of forgoing direct reproduction are relatively high. Building on previous work showing an association between longevity and cooperative breeding in birds [11,13,14], we are now able to distinguish between whether long life is a cause or a consequence of cooperative breeding. We found that long life makes cooperation more likely to evolve by comparing the life spans of the ancestors of cooperative and non-cooperative species, consistent with theoretical models of the evolution of rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, recent research has looked more deeply into the specific life-history features that might promote cooperative breeding (Arnold and Owens, 1998;Beauchamp, 2014). Efforts there have centred on finding evidence, among cooperatively breeding species, for the predominance of similar "Kselected" life-history traits.…”
Section: Introductionmentioning
confidence: 99%